Autologous Matrix-Induced Chondrogenesis (AMIC) for Isolated Retropatellar Cartilage Lesions: Outcome after a Follow-Up of Minimum 2 Years. (December 2021) - Waltenspül, Manuel; Suter, Cyrill; Ackermann, Jakob; Kühne, Nathalie; Fucentese, Sandro F.
Purpose: To evaluate autologous matrix-induced chondrogenesis (AMIC) for isolated focal retropatellar cartilage lesions and the influence of patellofemoral (PF) anatomy on clinical outcomes at a minimum of 2-year follow-up. Methods: Twenty-nine consecutive patients (31 knees) who underwent retropatellar AMIC with a mean age of 27.9 ± 11.0 years were evaluated at a follow-up averaging 4.1 ± 1.9 years (range, 2-8 years). Patient factors, lesion morphology, and patient-reported outcome measures, including Knee Injury and Osteoarthritis Outcome Score (KOOS), Tegner, Kujula score, and visual analogue scale (VAS) score were collected. PF anatomy was assessed on pre- and postoperative imaging, and subsequently correlated to outcome scores and failure to determine risk factors for poor outcome. Results: At final follow-up, the AMIC graft failed in 4 cases (12.9%) at a mean follow-up of 21 ± 14.1 months. Patients with failed grafts had a significantly smaller patellar and Laurins's PF angle than patients whose graft did not fail ( P = 0.008 and P = 0.004, respectively). Concomitant corrective surgery for patellar instability was performed in 29 knees (93.5%). Grafts that did not fail presented with an average Kujala score of 71.3 ± 16.9, KOOS Pain of 76.2 ± 16.6 and Tegner scores of 4.2 ± 1.8. The patellar angle was significantly associated with the patient's satisfaction level ( r = 0.615; P < 0.001). Conclusion: AMIC for retropatellar cartilage lesions in combination with concomitant corrective surgery for patellar instability results in low failure rate with satisfactory clinical outcome and patient satisfaction of almost 80% at mid-term follow-up. As most failures occurred in patients without concurrent tibial tubercle osteotomy and both a smaller patellar and Laurins's PF angle were associated with less favorable outcome, this study supports the growing evidence for the need of unloading retropatellar cartilage repair, when indicated. Level of Evidence: Case series; level of evidence, 4.